Draft Annual Plan 1988-89 Part II (Detail Schemes) Government of Mizoram - Planning Commission (Planning Commission, 1988)
Against the Approved. Outlay of Rs. 1,315.00 lakhs of 7th Plan (Crop Husbandry Rs. 1,200,00 lakhs, Agriculture Education - Rs. 15.00 lakhs and Agricultural Marketing; Rs. 100.00 lakhs) the expenditure during 1985-86 was Rs. 297.36 lakhs, during 1986-87 Rs. 299.90 lakhs, anticipated expenditure during 1987-88 Rs.299.00 lakhs and the proposed outlay for 1988-89 is Rs. 691.00 lakhs (Crop husbandry Rs. 651.00 lakhs, Agriculture Education Rs. 5.00 lakhs and Agricultural Marketing Rs. 35.00 lakhs.
Government of Mizoram, Planning and Programme Implementation Department